Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The last joint declaration of the highest authorities of the Food and Agriculture Organization of United Nations (IMF, World Bank, WFP, and OECD) highlighted three issues of global importance, considered at risk the food security, role of agriculture in economic growth, and poverty reduction caused directly by factors such as COVID 19, changes in climatic conditions in productive areas, water availability, pests and conflicts between various countries that are affecting food production systems and access to them.